Some Correlates of the HRD Climate: A Case Study of a Pharmaceutical Company - Jain, Silvie; Jain, V. K. (Prabandhan: Indian Journal of Management, 2013)
’Dynamic people build dynamic organizations, and effective employees contribute to the effectiveness of the organization. Competent and motivated people make things happen.’ HRD aims at constantly assessing competency requirements of different individuals to perform the jobs assigned to them effectively and provide opportunities for developing these competencies to prepare them for future roles in the organization. Every organization that wants to achieve its goals in terms of productivity, quality, profitability, stability, and growth and also increase organizational effectiveness, it must pay attention to the development of human resources in a systematic and planned manner. An optimal level of developmental climate is essential not only for the achievement of the above goals, but also for developing a motivated and dynamic workforce. For future growth, every organization must develop an organizational culture where the employees are given freedom to work, have a sense of belongingness, and an atmosphere of trust. The present study was undertaken to determine the correlation existing among the HRD climate variables of a pharmaceutical organization named as RXY Pharma Ltd.